Drug Quality Control Work in Drug Analysis and Research Unit: Observation During 1991-1995 (The East and Central African Journal of Pharmaceutical Sciences, 2020)
The Drug Analysis and Research Unit received and analyzed 262 drug samples over a five-year period 1991 to 1995. Samples were obtained from regulatory authorities, local industry, non-Governmental organizations, Hospitals and private practitioners. The samples analyzed, constituted 59.4% local and 40.6% imported. Failure to comply with quality specifications as set out in respective monographs was overall 17.5% representing 19.9% of local and 14.2% of imported products.
Keywords: Drugs, quality, DARU